Growing our own theatre staff: Practice development and education. Issue 5 (May 2018) - Cresswell, Becky; Davies, Corrina; Langlois, Sue; Richter, Dan
Royal Bournemouth & Christchurch Hospitals NHS Foundation Trust engaged in a quality improvement project aimed at improving quality and safety in theatres. The improvements delivered were recruitment to full staffing template, reduction in agency staffing to zero, and creating a theatre coordinator role to ensure safe staffing. The Practice Education Team was increased fivefold with no extra investment as a result of these improvements. Student satisfaction results amongst ODPs and nurses have increased alongside staff morale and productivity.